Inhibition of Phosphodiesterase-4 (PDE4) activity triggers luminal apoptosis and AKT dephosphorylation in a 3-D colonic-crypt model - Tsunoda, Toshiyuki; Ota, Takeharu; Fujimoto, Takahiro; Doi, Keiko; Tanaka, Yoko; Yoshida, Yasuhiro; Ogawa, Masahiro; Matsuzaki, Hiroshi; Hamabashiri, Masato; Tyson, Darren R.; Kuroki, Masahide; Miyamoto, Shingo; et al. (Molecular Cancer, 2012)
We previously established a three-dimensional (3-D) colonic crypt model using HKe3 cells which are human colorectal cancer (CRC) HCT116 cells with a disruption in oncogenic KRAS, and revealed the crucial roles of oncogenic KRAS both in inhibition of apoptosis and in disruption of cell polarity; however, the molecular mechanism of KRAS-induced these 3-D specific biological changes remains to be elucidated.